Middle Of The Road: Romania's Regional Policy In The Current Eu Programming Period - Daniela L. Constantin (European Regional Science Association (ERSA), 2012)
After less than two years from its accession to the EU, Romania was seriously hit by the global financial and economic crisis. Compared to other former transition countries, the turmoil was deeper and lasted longer and a modest recovery was recorded only in the second half of 2011, given deep internal vulnerabilities that amplified the impact of international shocks. Consequently, the Romanian regions have been also hit by the crisis, which induced an uneven distribution of its effects at regional scale, depending on the specific economic and social structures, regional specialisation degree, export orientation of economic activities, etc. The crisis has generated difficulties for the beneficiaries of the EU-funded projects – both local public administration and private firms - to provide the co-financing contribution, so that the Romanian Government has had to adopt a series of measures meant to support the implementation of the on-going Operational Programmes and the EU funds absorption process as well. This paper discusses the main developments of Romania's regional policy particularly in the 2009-2011 period, considered crucial years for the successful implementation of this policy. The economic, institutional, political factors that have influenced the regional policy during these years are analysed at the same time with the solutions proposed at the middle of the 2007-2013 programming period for the problems which the regional policy implementation is confronted with.
Keywords: R13; R28; R38; R58; 330; regional policy; Romania; Structural and Cohesion Funds; absorption; co-financing; implementation problems